SMART INFRARED THERAPY: OPTIMALISASI TIMER DAN SENSOR IOT UNTUK EFEKTIVITAS MAKSIMAL DALAM PENGEMBANGAN ALAT ELEKTROMEDIK - Primasyukra, Mhd Aldi; Ulina, Sri; Haslin, Sharfina; Syahputra, Muhammad Fahri; Malau, Roma Kristian (Fakultas Teknik, Universitas Riau Kepulauan, 2025)
Infrared therapy is widely used in medical rehabilitation; however, uncontrolled temperature, distance, and duration may reduce its effectiveness and increase patient risk. This study aims to implement a Smart Infrared Therapy system based on the ESP8266 microcontroller, integrating the MLX90614 temperature sensor, the HC-SR04 distance sensor, and the Blynk IoT platform to enhance safety and precision. The system is designed to monitor skin surface temperature and patient distance in real-time, control therapy duration through an automatic timer, and provide immediate notifications when safety thresholds are exceeded. The evaluation focused on three main aspects: temperature measurement accuracy, distance detection accuracy, and IoT–timer integration performance. Results show that the MLX90614 sensor achieved a maximum error of 0.82% with a response time of